Bridging Borders through Financial Technology: Analysis of the Factors that Influence the Adoption of Fintech MSMEs in Indonesia's Front Yard - Warsiningsih, Tina; Khumaira, Shahnaz; Darmasari, Elita; Wijaya, Nova; Putranto, Galih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Bridging Borders through Financial Technology: An Analysis of Determinants of Fintech Adoption among MSMEs in Indonesia's Border Regions. This study aims to identify and analyze the factors that influence the intention to adopt financial technology among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's border regions. As fintech services continue to grow rapidly, a deep understanding of the drivers and barriers to technology adoption is crucial for enhancing financial inclusion in the SME sector, particularly in border regions with unique socio-economic characteristics. The study employs a quantitative approach using Partial Least Squares Structural Equation Modeling to analyze data from 300 SME respondents across various border regions in Indonesia. The variables studied include perceived usefulness, perceived ease, social influence, sense of security, and digital financial literacy, with control variables such as education level, age, residence, and proximity to the border. The results indicate that all independent variables have a significant positive influence on the intention to adopt fintech, with a stronger effect on SMEs in border regions. Digital financial literacy was found to moderate the relationships between variables, while proximity to the border strengthens all relationships in the model. This study contributes to the development of an inclusive and sustainable fintech ecosystem in Indonesia's border regions.